Malaria epidemiology in Kilifi, Kenya during the 21st century: What next? - Von Seidlein, L; Knudsen, J (Public Library of Science, 2015)
In this issue of PLOS Medicine, Polycarp K. Mogeni and colleagues present a unique dataset collected from 69,104 children aged from 3 months to 13 years admitted over the last 25 years to Kilifi County Hospital, Kenya. In 1998, 56% of the children were admitted with malaria, presumably mostly caused by Plasmodium falciparum. By 2009, just 7% of the children were admitted with malaria. Although malaria burden is much reduced, it remains unacceptably high; what can be done to reduce malaria transmission further?